Duodenal strongyloidiasis infection mimicking lymphangiectasia - Bilal, Muhammad; Ahmed, Nisar (Asian Journal of Medical Sciences, 2017)
Strongyloides stercoralis infection usually causes a chronic asymptomatic intestinal infection or otherwise non-specific generalized complaints. The diagnosis of strongyloidiasis by routine stool examination is very limited. Endoscopic findings in strongyloidiasis range from mucosal granularity to friable edema to frank ulceration or Small bowel obstruction secondary to intense infestation. The pathological examination of tissue biopsy and aspirate can give the definitive diagnosis. We report a case of middle age patient who presented with the symptoms of weight loss and diarrhea. On evaluation, upper GI endoscopy (EGD) showed the findings of lymphangiectasia but biopsy findings were consistent with strongyloidiasis which was successfully treated with Ivermectin 200 μg/kg, given for two days. Asian Journal of Medical Sciences Vol.8(5) 2017 98-100